Upping the Ante : The Equilibrium Effects of Unconditional Grants to Private Schools - Andrabi, Tahir (World Bank, Washington, DC, 2018)
This paper tests for financial constraints as a market failure in education in a low-income country. In an experimental setup, unconditional cash grants are allocated to one private school or all private schools in a village. Enrollment increases in both treatments, accompanied by infrastructure investments. However, test scores and fees only increase in the setting of all private schools along with higher teacher wages. This differential impact follows from a canonical oligopoly model with capacity constraints and endogenous quality: greater financial saturation crowds-in quality investments. The findings of higher social surplus in the setting of all private schools, but greater private returns in the setting of one private school underscore the importance of leveraging market structure in designing educational subsidies.